(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Parametric study on pressure-swing adsorption cycle desiccant dehumidification system is a continuous engineering task with the aim of analyzing its effects and attains target quality of dry air for an industrial process. An experimental setup is developed with a dehumidification tower, regeneration tower,and flow control valve.The effect of process air inlet moisture content, cycle time ratio, and regeneration air flow rate on the adsorption performance is studied to evaluate the potential of the dehumidification system suitable for drying applications. The optimal dehumidification parameters are found, and a regression equation is also developed for the process. It is concluded that, process air inlet moisture is the most influencing parameter compared to regeneration air flow rate and cycle time ratio for the silica gel desiccant dehumidification system.